Trunk injuries in athletes - Gundersen, A.; Borgstrom, H. D.; McInnis, K. C. (Current Sports Medicine Reports, 2021)
Trunk pain is a common cause of performance limitation and time away from sport in athletes. However, atraumatic trunk injuries are underrepresented in medical literature and underrecognized clinically. Delays in diagnosis and initiation of appropriate treatment can increase injury morbidity and return-to-play time. Currently, evidence-based guidelines for diagnosis and treatment of trunk pain in athletes are limited. Thus, we provide an overview of atraumatic sport-related injuries to the thoracic spine (disc herniation, scoliosis, kyphosis), ribcage (bone stress injury, costochondritis, Tietze syndrome, slipping rib syndrome, costovertebral or costotransverse joint dysfunction), and chest and abdominal wall musculature (intercostal, serratus anterior, oblique strains, regional myofascial pain), highlighting sport-specific biomechanical considerations. We aim to increase awareness of these causes of trunk pain among sports medicine providers in an effort to guide diagnostic and treatment recommendations that will ultimately improve overall musculoskeletal health in athletes.